Academic work and performativity - Kenny, John (Higher Education, 2016)
Neoliberal reforms in higher education have resulted in corporate managerial practices in universities and a drive for efficiency and productivity in teaching and research. As a result, there has been an intensification of academic work, increased stress for academics and an emphasis on accountability and performativity in universities. This paper critically examines these developments in institutions and draws on evidence from universities across the sector and a detailed case study in one university to identify the impacts of these changes on academic work. Given its ubiquity and the link of academic productivity to institutional experience, the paper argues that assumptions underpinning academic performance management need to be rethought to recognise the fundamentally intrinsic motivational nature of academic work. The paper explores the effects of performance management on individual academics as a case study in one institution and proposes a re-design of academic performance management to improve productivity based on the evidence.